2021
DOI: 10.1111/ppa.13364
|View full text |Cite
|
Sign up to set email alerts
|

Molecular and physiological characterization of ArabidopsisColletotrichum gloeosporioides pathosystem

Abstract: Anthracnose is a destructive disease that affects a wide range of crop plants especially in tropical and subtropical regions. Colletotrichum spp. are the major pathogens causing anthracnose. In this study, we collected and identified the pathogen from diseased samples of Stylosanthes, a major tropical forage crop. The ability of the pathogen to naturally infect Arabidopsis thaliana was examined. Sequence analysis of ITS, ACT, CHS, and GAPDH genes showed the pathogen to be Colletotrichum gloeosporioides sensu l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…The seedlings were grown in a greenhouse with an average temperature of 28 °C for approximately 3 weeks [ 9 ]. Colletotrichum gloeosporioides strain WC-02 was used in this study and described previously [ 39 ]. The inoculation of C. gloeosporioides was performed according to the previous study [ 9 , 25 ].…”
Section: Methodsmentioning
confidence: 99%
“…The seedlings were grown in a greenhouse with an average temperature of 28 °C for approximately 3 weeks [ 9 ]. Colletotrichum gloeosporioides strain WC-02 was used in this study and described previously [ 39 ]. The inoculation of C. gloeosporioides was performed according to the previous study [ 9 , 25 ].…”
Section: Methodsmentioning
confidence: 99%
“…Basic research. Studies on S. guianensis conducted in China, including CIAT 184 as a prominent example, addressed: development of molecular markers for diversity analysis (Ding Xipeng et al 2015), genetic transformation (Guo Pengfei et al 2019;Wang Linjie et al 2023), molecular and gene expression mechanisms involved in abiotic and biotic stress tolerances [chilling, drought and salt (Zhou Biyan et al 2005a, 2005bYang Jinfen and Guo Zhenfei 2007;Zhou Biyan and Guo Zhenfei 2009;Lu Shaoyun et al 2013;Bao Gegen et al 2016;Li Kailong et al 2018), nutrients (Du Yumei et al 2009Jiang Caode et al 2018;Liu Pandao et al 2019;Chen Zhijian et al 2021;Song Jianling et al 2022) and anthracnose (Wang Hui et al 2017;Gao Mengze et al 2021;Jiang Lingyan et al 2021)].…”
Section: Genetic Diversity and New Cultivarsmentioning
confidence: 99%
“…Two Arabidopsis MAPKs in group A (AtMPK3 and AtMPK6) were identified to be involved in disease resistance against C. gloeosporioides (Gao et al, 2021 ). Genetic studies have shown that mpk3-1, mpk6-2 mutants are more susceptible to both weak and aggressive isolates of C. gloeosporioides .…”
Section: Protein Kinases In Host Plantsmentioning
confidence: 99%
“…Genetic studies have shown that mpk3-1, mpk6-2 mutants are more susceptible to both weak and aggressive isolates of C. gloeosporioides . In addition, marker genes of MAPK pathways, AtWRKY33 and AtWRKY40 , are significantly up-regulated in response to C. gloeosporioides pathogens, and the less virulent isolates trigger even higher induction of marker genes (Gao et al, 2021 ). These results suggest a positive role of AtMPK3/6 in regulating resistance against Colletotrichum .…”
Section: Protein Kinases In Host Plantsmentioning
confidence: 99%